2021
DOI: 10.1111/jonm.13471
|View full text |Cite
|
Sign up to set email alerts
|

Association between workplace bullying and nurses' professional quality of life: The mediating role of resilience

Abstract: Aim We aim to determine workplace bullying in relation to the professional quality of life of nurses and the mediating role of resilience between workplace bullying and the professional quality of life. Background Workplace bullying is an increasingly serious problem worldwide and deleteriously affects the occupational health and quality of life of nurses. However, it has not attracted adequate managerial attention. Method A cross‐sectional study was conducted using a sample of 493 clinical nurses from two ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 48 publications
(55 reference statements)
5
19
1
Order By: Relevance
“…Speci cally, the more severe the workplace bullying that nurses experienced, the less pleasure and satisfaction they felt at work, and the higher the level of burnout and secondary trauma they incurred. These ndings are consistent with Jie Peng's study [12], which indicated that long-term exposure to bullying work environments, such as harassment, offense, and isolation, would increase nurses' physical and mental consumption, leading to a decrease in their work accomplishment and compassion satisfaction. At the same time, it would exacerbate mental and emotional burnout, helplessness, anxiety, and other adverse psychological reactions, and aggravate the secondary trauma of nurses [12,16].…”
Section: Intermediary Effect Testsupporting
confidence: 88%
See 1 more Smart Citation
“…Speci cally, the more severe the workplace bullying that nurses experienced, the less pleasure and satisfaction they felt at work, and the higher the level of burnout and secondary trauma they incurred. These ndings are consistent with Jie Peng's study [12], which indicated that long-term exposure to bullying work environments, such as harassment, offense, and isolation, would increase nurses' physical and mental consumption, leading to a decrease in their work accomplishment and compassion satisfaction. At the same time, it would exacerbate mental and emotional burnout, helplessness, anxiety, and other adverse psychological reactions, and aggravate the secondary trauma of nurses [12,16].…”
Section: Intermediary Effect Testsupporting
confidence: 88%
“…That is to say, coping style is the intermediary variable between job stress and burnout. The study found that workplace bullying hurt nurses' compassion satisfaction and had a positive impact on empathy fatigue [12], and coping styles had a signi cant predictive effect on nurses' professional quality of life [19]. So far, there are no reports regarding the role of coping styles as mediating variables in workplace bullying and professional quality of life among nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that examined sexual harassment, bullying, and incivility did not specify the perpetrator (anonymous). Eight studies reported perpetrators (Cheung et al, 2017; Ko et al, 2020; Kwok et al, 2006; Pai & Lee, 2011; Peng et al, 2022; Sun et al, 2017; J. H. Yang et al, 2019; Zeng et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies ( K = 27) used the Maslach Burnout Inventory (Maslach & Jackson, 1981) to assess the burnout symptoms. Two articles (Kobayashi et al, 2020; Peng et al, 2021) utilized the Professional Quality of Life scale, while only one (Bae et al, 2021) used the Tedium Scale. Of these, 10 studies reported the prevalence of burnout among nurses after exposure to WPV.…”
Section: Resultsmentioning
confidence: 99%